2019
DOI: 10.1186/s12964-019-0329-3
|View full text |Cite
|
Sign up to set email alerts
|

A signalling cascade involving receptor-activated phospholipase A2, glycerophosphoinositol 4-phosphate, Shp1 and Src in the activation of cell motility

Abstract: Background Shp1, a tyrosine-phosphatase-1 containing the Src-homology 2 (SH2) domain, is involved in inflammatory and immune reactions, where it regulates diverse signalling pathways, usually by limiting cell responses through dephosphorylation of target molecules. Moreover, Shp1 regulates actin dynamics. One Shp1 target is Src, which controls many cellular functions including actin dynamics. Src has been previously shown to be activated by a signalling cascade initiated by the cytosolic-phospholi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 66 publications
0
15
0
Order By: Relevance
“…However, the involvement of other eicosanoids and bioactive lipids such as lysophospholipids or platelet-activating factor cannot be ruled out. Other possible mechanisms where activation of cPLA2α facilitates migration include the generation of glycerophosphoinositol 4-phosphate, which activates Shp1 and Src and thus impacts actin remodeling in fibroblasts [38] and lysophosphatidic acid, as seen in ovarian cancer cells [39].…”
Section: Resultsmentioning
confidence: 99%
“…However, the involvement of other eicosanoids and bioactive lipids such as lysophospholipids or platelet-activating factor cannot be ruled out. Other possible mechanisms where activation of cPLA2α facilitates migration include the generation of glycerophosphoinositol 4-phosphate, which activates Shp1 and Src and thus impacts actin remodeling in fibroblasts [38] and lysophosphatidic acid, as seen in ovarian cancer cells [39].…”
Section: Resultsmentioning
confidence: 99%
“…Activation of Syk, in turn, promotes an intracellular signaling cascade that eventually leads to phosphorylation and activation of the LAT [37], resulting in the phosphorylation of PLCγ2 [38]. PLCγ2 then acts as an adapter protein for PKC, which finally leading to the activation of downstream effectors and contribute to the platelet granule secretion [39]. In order to clarify the mechanism of Fruitflow inhibiting platelet granule release, we investigated the activation of Src/PLCγ2/PKC signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Our group has recently shown that Shp1 regulates actin remodeling and cell motility through yet another mechanism involving Src kinase (45). We identified Shp1 as the cellular receptor of the bioactive metabolite glycerophosphoinositol-4 phosphate (GroPIns4P) and as a novel component in the signaling pathway activated by EGF to control cell motility (45).…”
Section: Shp1 In Cell Motility and Invasionmentioning
confidence: 99%
“…Our group has recently shown that Shp1 regulates actin remodeling and cell motility through yet another mechanism involving Src kinase (45). We identified Shp1 as the cellular receptor of the bioactive metabolite glycerophosphoinositol-4 phosphate (GroPIns4P) and as a novel component in the signaling pathway activated by EGF to control cell motility (45). In NIH3T3 cells, activation of the EGF receptor leads to activation of the cytosolic phospholipase A 2 and results in the hydrolysis of phosphatidylinositol-4 phosphate and formation of GroPIns4P that binds to Shp1 and promotes its association with Src.…”
Section: Shp1 In Cell Motility and Invasionmentioning
confidence: 99%
See 1 more Smart Citation